Theoretical insights into the metal chelating and antimicrobial properties of the chalcone based Schiff bases. Issue 8 (24th May 2019) - Pitchumani Violet Mary, C.; Shankar, R.; Vijayakumar, S.
ABSTRACT: The emergence of multi-drug resistant pathogens in infectious disease conditions accentuates the need for the design of new classes of antimicrobial agents that could defeat the multidrug resistance problems. As a new class of molecules, the Heterocyclic Schiff base is of considerable interest, owing to their preparative accessibility, structural flexibilities, versatile metal chelating properties, and inherent biological activities. In the present study, CAM-B3LYP/LANL2DZ and M062X/DEF2-TZVP level of density functional method is used to explore the complexation of chalcone based Schiff base derivatives by Co 2+, Ni 2+, Cu 2+, and Zn 2+ metal ions. The HL(1-3)-Co 2+, HL(1-3)-Ni 2+ and HL(1-3)-Zn 2+ complexes formed the distorted tetrahedral geometry. Whereas, the HL(1-3)-Cu 2+ complexes prefers distorted square-planar geometry. The BSSE corrected interaction energies of the studied complexes reveals that Cu 2+ ion forms the most stable complexes with all three chalcone based Schiff bases. Of the three Schiff bases studied, the HL2 Schiff base acts as a potent chelating agent and forms the active metal complexes than the HL1 and HL3 Schiff bases. Further, the strength of the interaction follows the order as Cu 2+  > Ni 2+  > Co 2+  > Zn 2+ . The QTAIM analysis reveals that the interaction between the metal ions and coordinating ligand atoms are electrostatic dominant. The metal interaction increases the π-delocalisation of electrons over the entire chelate. Hence, the antimicrobial activity of the metal complexes is more effective than the free Schiff bases. Moreover, the HL(1-3)-Cu 2+ complexes shows higher antimicrobial activities than the other complexes studied.